2021
DOI: 10.1186/s12955-021-01847-0
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life profiles and their dimension-specific associated factors among Malaysian stroke survivors: a cross sectional study

Abstract: Background Apart from maximizing functional abilities and independence after stroke, improving overall health-related quality of life (HRQoL) should also become part of the stroke treatment and rehabilitation process goals. This study aimed to assess the HRQoL profiles and explore the dimension-specific associated factors of HRQoL among stroke survivors. Methods This was a cross-sectional study of stroke survivors attending post-stroke care clinics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 57 publications
4
15
1
2
Order By: Relevance
“…Mobility and physical functioning have been identified as independent predictors of HRQoL in stroke patients (Naess et al, 2006;Valeros, 2017;Thayabaranathan et al, 2018;Wong et al, 2021). Our study confirmed these findings showing mRS and Barthel index to have strong or moderate correlations with the various EQ-5D-5L dimensions.…”
Section: Association Of Physical Functioning and Hrqolsupporting
confidence: 88%
See 1 more Smart Citation
“…Mobility and physical functioning have been identified as independent predictors of HRQoL in stroke patients (Naess et al, 2006;Valeros, 2017;Thayabaranathan et al, 2018;Wong et al, 2021). Our study confirmed these findings showing mRS and Barthel index to have strong or moderate correlations with the various EQ-5D-5L dimensions.…”
Section: Association Of Physical Functioning and Hrqolsupporting
confidence: 88%
“…Among the participants in our study, majority did not attain college level education, were unemployed and had income less than the monthly minimum wage stipulated in the country. Although these socio-economic factors were not found to be predictors of poor HRQoL in the present study, previous studies have reported female gender, low educational attainment and poor socio-economic status as part of a complex network of risk factors associated with HRQoL in stroke survivors (Naess et al, 2005;Phan et al, 2019;Wong et al, 2021). Studies with larger sample sizes are required to further evaluate these important factors and their influence on the HRQoL of young adult stroke patients.…”
Section: Other Predictors Of Poor Health-related Quality Of Lifecontrasting
confidence: 62%
“…A previous UK study looking for factors influencing the quality of life of stroke survivors reveals that diabetes and ischemic heart disease were significant factors [ 27 ]. Another study of Malaysians shows that obesity, smoking status, malnutrition risk, and physical activity level had an effect on the physical dimensions of the quality of life [ 28 ]. This study showed the relationship between overall cardiovascular health and quality of life in stroke survivors from the nationally representative cross-sectional survey.…”
Section: Discussionmentioning
confidence: 99%
“…En cuanto al impacto de tipo mental, la ansiedad/depresión con un 66,70 % fue la reportada en mayor proporción. En el estudio de Wong y col. (Wong HJ, Lua PL, Harith S, Ibrahim KA, 2021) se reportó un 51 % de ansiedad/depresión; en el de Comín et al (Comín-Coleta J, Anguita M, Formiga F, Almena L, Crespo-Leirog MG, Manzano L, 2016) ansiedad/depresión fue de 48,90 % mientras que en el de Lens y col. (Lens C, Demeestere J, Vanhaecht K, Lemmens R, 2021) el 52,46 % de los pacientes padecieron de ansiedad. De todos los factores psicológicos, la depresión es el que ha sido objeto de mayor atención para la investigación durante la última década.…”
Section: Discussionunclassified